Pattern of Intraocular Pressure Fluctuation in Uveitic Eyes Treated with Corticosteroids. (April 2014) - Shrestha, Sneha; Thapa, Madhu; Shah, Dev Narayan
Abstract Purpose: To determine IOP fluctuation in uveitic eyes treated with corticosteroids. Design: Prospective Observational Study. Method: Study of 116 consecutive new uveitis patients visiting Uveitis clinic, BPKLCOS. IOP was meticulously monitored. Data was analyzed in SPSS-16 using paired samples 't-test'. Results: The mean IOP in all patients at presentation, at 1 week, 3 weeks and 6 weeks were respectively 14.66 mmHg, 14.72 mmHg, 14.75 mmHg and 14.93 mmHg. This progressive IOP rise was not statistically significant. Ocular hypertension was seen in 20% eyes; 64.5% were due to corticosteroids. Steroid-induced ocular hypertension was seen in 37.03% of oral group, 14.28% of posterior subtenon group, 8.57% of topical group. Antiglaucoma medications were started in 61.2% of the cases with raised IOP. None had to undergo glaucoma filtering surgery. Conclusion: Incidence of ocular hypertension in uveitic eyes was 20% in this study.Majority of them was corticosteroid induced. Timely medical treatment averted the necessity of surgical intervention for IOP control.